2005
DOI: 10.4049/jimmunol.175.1.124
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of CD40/CD40-Ligand Interactions in a Retinal Autoimmunity Model Results in Protection without Tolerance

Abstract: We examined the role of CD40/CD40L interactions on the development of experimental autoimmune uveoretinitis (EAU), a cell-mediated, Th1-driven autoimmune disease that serves as a model for autoimmune uveitis in humans. EAU-susceptible B10.RIII mice immunized with the retinal autoantigen interphotoreceptor retinoid binding protein in CFA and treated with anti-CD40L Ab (MR1) had reduced incidence and severity of disease. Real-time PCR analysis revealed that the innate and adaptive responses of protected mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…For Ag-specific lymphocyte proliferation and cytokine production, spleen and draining lymph nodes (LNs; inguinal and iliac) of individual mice (4 -5 per group) were collected 3 wk after immunization. Cells were pooled within the group and were stimulated with graded concentrations of Ag in triplicate cultures of 0.2 ml, essentially as described (22). Proliferation of LN cells was determined by [ 3 H]thymidine incorporation.…”
Section: Ag-specific Immunological Responsesmentioning
confidence: 99%
“…For Ag-specific lymphocyte proliferation and cytokine production, spleen and draining lymph nodes (LNs; inguinal and iliac) of individual mice (4 -5 per group) were collected 3 wk after immunization. Cells were pooled within the group and were stimulated with graded concentrations of Ag in triplicate cultures of 0.2 ml, essentially as described (22). Proliferation of LN cells was determined by [ 3 H]thymidine incorporation.…”
Section: Ag-specific Immunological Responsesmentioning
confidence: 99%
“…CD40 is a regulator of inflammatory disorders, and studies using nonocular cells revealed that the CD40 induces NOS2 and COX-2, triggers chemokine production (MCP-1, IL-8, and MIP-2), and up-regulates ICAM-1 (14 -19). Immunization with retinal Ag results in the generation of a T cell response in peripheral lymphoid tissues, a process that is dependent on CD40 and leads to T cell-mediated experimental autoimmune uveoretinitis (20,21). However, whether CD40 in the retina is involved in other retinopathies is unknown.…”
mentioning
confidence: 99%
“…CD40L blockade inhibited innate responses to immunization and reduced priming. 13 Fas (gld; TNFRSF6) or FasL (lpr) deficient mice developed lower incidence and severity following EAU induction compared with wild-type controls. The underlying mechanisms for this resistance were not defined, but bone marrow chimaeras demonstrated that normal expression of Fas and FasL on hemopoietic cells of the immune system, but not on ocular tissue, was required for the induction.…”
Section: J Calder and E C Y Wangmentioning
confidence: 99%
“…Perhaps of greatest significance, all of our findings highlight the differences between DR3 and other members of the TNFR superfamily in the induction of ocular inflammation. Apart from the role of TNFR1 described above, Fas, 11 CD40L, 13 and 4-1BBL 14 have also been implicated in the pathogenesis of EAU. Mice deficient in 4-1BB (TNFRSF9) are susceptible to EAU, however, treatment with agonistic anti-4-1BB mAb alleviated disease through the expansion of IFNγ-producing CD11c + CD8 + T cells.…”
Section: J Calder and E C Y Wangmentioning
confidence: 99%
See 1 more Smart Citation